2020
DOI: 10.1002/jbmr.4226
|View full text |Cite
|
Sign up to set email alerts
|

Lubricin Contributes to Homeostasis of Articular Cartilage by Modulating Differentiation of Superficial Zone Cells

Abstract: Lubricin encoded by the proteoglycan 4 (Prg4) gene is produced from superficial zone (SFZ) cells of articular cartilage and synoviocytes, which is indispensable for lubrication of joint surfaces. Loss‐of‐function of human and mouse Prg4 results in early‐onset arthropathy accompanied by lost SFZ cells and hyperplastic synovium. Here, we focused on increases in the thickness of articular cartilage in Prg4‐knockout joints and analyzed the underlying mechanisms. In the late stage of articular cartilage development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
(66 reference statements)
2
27
0
Order By: Relevance
“…As described above, Prg4 knockout mice display increased articular cartilage thickness [ 7 ]; however, the underlying molecular mechanism was unknown. We confirmed that the SFZ disappeared at eight weeks in the Prg4 knockout mice, and their cartilage was significantly thicker than that of wild-type (WT) mice [ 15 ]. In addition to the enhanced cartilage degeneration caused by the SFZ disappearance, ectopic endochondral ossification was observed with aging in the knockout mice [ 15 ].…”
Section: The Roles Of Prg4 As a Signaling Moleculementioning
confidence: 58%
See 2 more Smart Citations
“…As described above, Prg4 knockout mice display increased articular cartilage thickness [ 7 ]; however, the underlying molecular mechanism was unknown. We confirmed that the SFZ disappeared at eight weeks in the Prg4 knockout mice, and their cartilage was significantly thicker than that of wild-type (WT) mice [ 15 ]. In addition to the enhanced cartilage degeneration caused by the SFZ disappearance, ectopic endochondral ossification was observed with aging in the knockout mice [ 15 ].…”
Section: The Roles Of Prg4 As a Signaling Moleculementioning
confidence: 58%
“…We confirmed that the SFZ disappeared at eight weeks in the Prg4 knockout mice, and their cartilage was significantly thicker than that of wild-type (WT) mice [ 15 ]. In addition to the enhanced cartilage degeneration caused by the SFZ disappearance, ectopic endochondral ossification was observed with aging in the knockout mice [ 15 ]. Cell tracking indicated that Prg4 homo-knockout SFZ cells abnormally expand to the DZ layers, compared with Prg4 hetero-knockout cells [ 15 ].…”
Section: The Roles Of Prg4 As a Signaling Moleculementioning
confidence: 58%
See 1 more Smart Citation
“…BMP signaling is crucial for skeletogenesis, particularly for endochondral development. On the contrary, TGFβ signaling is crucial for joint development [48,49] and homeostasis of articular cartilage [42,50,51]. In fact, TGFβ1 is constantly supplied to the synovial fluid from cartilage and synovium [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…It contributes to the highly lubricated cartilage surface [8] and is critical for SZ integrity since mice lacking Prg4 exhibit a loss of cartilage structure, change in stiffness and frictional properties [9] and develop cartilage wear as they age [10,11]. Mechanistically this may occur via the nuclear factor-κB-matrix metalloproteinase 9-transforming growth factor beta (NFκB-MMP9-TGFβ) axis since lubricin is increased by TGFβ and lubricin suppresses SZ MMP9 expression preventing chondrocyte differentiation [7,12]. Recently, β-catenin signalling has also been linked to lubricin's role in maintaining cartilage surface integrity since deletion of β-catenin in Prg4-expressing SZ cells leads to failure of the SZ and enhanced progression of osteoarthritis (OA) [13].…”
Section: Introductionmentioning
confidence: 99%